Optimal planning of charging stations and electric vehicles traffic assignment: a bi-level approach. Issue 2 (2020) - Ferro, G.; Minciardi, R.; Parodi, L.; Robba, M.
Abstract: A new bi-level approach is proposed for the location and sizing of charging stations, considering both the transportation and energy demands. The lower level considers the User Equilibrium traffic assignment conditions for Electric Vehicles (EVs) which are derived and inserted as constraints in the overall optimization problem. The higher level presents the formalization of an optimization problem for the optimal planning of locations, sizes and unit prices of a set of new charging stations in a territory characterized by the presence of an already existing set of charging stations. A case study in the Genoa Municipality is considered for the application of the proposed model.